Mitochondrial DNA Variants in a Portuguese Population of Patients with Alzheimer’s Disease - Grazina, M (2013)
Alzheimer's disease (AD) is the most common neurodegenerative disorder associated with dementia in late adulthood. Mitochondrial respiratory chain impairment has been detected in the brain, muscle, fibroblasts and platelets of AD patients, indicating a possible involvement of mitochondrial DNA (mtDNA) in the etiology of the disease. Several reports have identified mtDNA mutations in AD patients, but there is no consensual opinion regarding the cause of the impairment. We have studied mtDNA NADH dehydrogenase subunit 1 nucleotides 3337-3340, searching for mutations. Our study group included 129 AD patients and 125 healthy age-matched controls. We have found alterations in two AD patients: one had two already known mtDNA modifications (3197 T-C and 3338 T-C) and the other a novel transition (3199 T-C) which, to our knowledge, has not been described before.